2021
DOI: 10.21203/rs.3.rs-433108/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The pathways from perceived discrimination to self-rated health among the Chinese diaspora during the COVID-19 pandemic: investigation of the roles of depression, anxiety, and social support

Abstract: Background. Research indicates the adverse impacts of perceived discrimination on health, and discrimination inflamed by the COVID-19 pandemic, a type of social exclusion, could affect the well-being of the Chinese diaspora. The relationship and pathways of perceived discrimination’s effect on health among the Chinese diaspora in the context of the pandemic were examined to contribute to the literature on discrimination in this population under the global public health crisis.Methods. We analysed data from 705… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…For example, Pascoe and Smart Richman (2009) suggest that perceptions of chronic exposure to discrimination frequently activate stress responses that can lead to a consistent negative emotional state. In response to this, research also shows that having friends or family to talk to after exposure to discrimination negates development of mental health symptoms potentially through validating an individual's experience and helping rebuild or enhance their feelings of self-worth (Chen et al, 2021;Pascoe & Smart Richman, 2009;Smart Richman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Pascoe and Smart Richman (2009) suggest that perceptions of chronic exposure to discrimination frequently activate stress responses that can lead to a consistent negative emotional state. In response to this, research also shows that having friends or family to talk to after exposure to discrimination negates development of mental health symptoms potentially through validating an individual's experience and helping rebuild or enhance their feelings of self-worth (Chen et al, 2021;Pascoe & Smart Richman, 2009;Smart Richman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies among diverse ethno‐racial groups in the United States have shown negative coping behaviours as mediators between discrimination and health. For example, Chen and Yang (2014) found that racial discrimination was associated with increased smoking that in turn led to worsening mental health symptoms and subsequent poorer self‐rated health, while higher levels of social support facilitated better mental health (Chen et al, 2021; Chen & Yang, 2014). Additionally, a study among Latinx youth found that experiences of racial microaggressions were associated with increased utilisation of detachment coping which led to higher levels of psychological distress, with adaptive coping buffering the discrimination‐health relationship (Ayala, 2019).…”
Section: Discrimination Acculturative Stress and Coping Among African...mentioning
confidence: 99%
See 1 more Smart Citation